2019
DOI: 10.1590/s1678-9946201961023
|View full text |Cite
|
Sign up to set email alerts
|

Ozone against Pseudomonas aeruginosa biofilms in contact lenses storage cases

Abstract: Pseudomonas aeruginosa is associated with ocular infections such as keratitis. Multipurpose contact lens solutions can be used for washing, disinfection and storage of contact lenses, however, P. aeruginosa biofilm disinfection by this method is unsatisfactory. The present study aimed to investigate the effectiveness of ozonated water in reducing P. aeruginosa colony count. Lenses kept in storage cases were contaminated with P. aeruginosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In the last few years, a renewed interest in the therapeutic potential of ozone has emerged. In particular, the focus is on the ability to promote wound healing, to attenuate the adverse effects of inflammation by reducing the oxidative activities of inflammatory cells, to express antimicrobial activities against various bacterial species and mycetes pathogenic for humans, and also against biofilm-producing and antibiotic-resistant bacteria, thus offering chances of overcoming antibiotic-resistance issues [30][31][32][33][34][35][36][37][38][39] (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, a renewed interest in the therapeutic potential of ozone has emerged. In particular, the focus is on the ability to promote wound healing, to attenuate the adverse effects of inflammation by reducing the oxidative activities of inflammatory cells, to express antimicrobial activities against various bacterial species and mycetes pathogenic for humans, and also against biofilm-producing and antibiotic-resistant bacteria, thus offering chances of overcoming antibiotic-resistance issues [30][31][32][33][34][35][36][37][38][39] (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…from 92.93-97.31% CFU/cm 2 ), ozone reduces this Gram negative bacterial bio lms from surfaces to 7.34 log (i.e. 99.99999% CFU/cm 2 ) [23]. Ozone is able to eradicate bacteria from ICUs as well as SARS-CoV2.…”
Section: Are There Major Confounders In the O Cial Count Of Covid-19 mentioning
confidence: 98%
“…Hofmaenner and colleagues, reported that many Gram negative bacteria are much more present in sinks and siphons of ICUs than SARS-CoV2 [9]. Ozone is completely enabled to kill Pseudomonas aeruginosa from surfaces and objects [23]. A recent paper by Matteo Bassetti's group investigated the incidence of pneumonias, which he called ventilator associated pneumonia (VAP), caused by HAI-infected ventilator devices [3].…”
Section: Are There Major Confounders In the O Cial Count Of Covid-19 mentioning
confidence: 99%
“…16 Ozone has powerful antimicrobial activity against bacteria and fungi, such as Candida albicans , Streptococcus mutans , and Pseudomonas aeruginosa . 1719 A recent study 20 demonstrated that an immersion of the denture base with acrylic resins in ozonated water that was prepared by a home ozone generator could inhibit Candida growth and colonization on the denture base acrylic resins. However, it must be investigated to ensure that ozonated water has no significant negative effect on the corrosion resistance of the Co-Cr frameworks.…”
Section: Introductionmentioning
confidence: 99%